Fake accounts : a novel - Oyler, Lauren (Catapult, 2021)
On the eve of Donald Trump's inauguration, a young woman snoops through her boyfriend's phone and makes a startling discovery: he's an anonymous internet conspiracy theorist, and a popular one at that. Already fluent in internet fakery, irony, and outrage, she's not exactly shocked by the revelation. Actually, she's relieved- he was always a little distant- and she plots to end their floundering relationship while on a trip to the Women's March in DC. But this is only the first in a series of bizarre twists that expose a world whose truths are shaped by online lies. Suddenly left with no reason to stay in New York and increasingly alienated from her friends and colleagues, our unnamed narrator flees to Berlin, embarking on her own cycles of manipulation in the deceptive spaces of her daily life, from dating apps to expat meetups, open-plan offices to bureaucratic waiting rooms. She begins to think she can't trust anyone- shouldn't the feeling be mutual? Narrated with seductive confidence and subversive wit, Fake Accounts challenges the way current conversations about the self and community, delusions and gaslighting, and fiction and reality play out in the internet age -- Provided by publisher.